Aumento da regeneração de Manihot esculenta por genes morfogênicos após edição genética - Rosana Alessandra Segatto (2023)
The Growth Regulating Factor (GRF) and its Interacting Factor (GIF) have been shown to stimulate regeneration of transgenic plants, with studies reporting increased transformation efficiency in multiple species including wheat, beet and citrus. The present work evaluated the effects of overexpressing GRF4- GIF1 and GRF5 on the regeneration of transgenic plants in cassava (Manihot esculenta Crantz). Effects of GRF4-GIF1 and GRF5 sequences derived from Vitis vinifera and Arabidopsis thaliana were assessed by cloning expression cassettes under control of strong constitutive promoters. Friable embryogenic callus from cassava varieties 60444 and NASE 13 were transformed with Agrobacterium tumefaciens strains LBA4404 and LBA4404 THY- and multiple independent transgenic plant lines recovered. Expression of the morphogenic genes did not enhance transformation efficiency above the GFP control, nor efficiency or timing of somatic embryo regeneration or whole plant recovery. Organogenesis experiments were carried out to observe effects of these genes on morphogenesis from petiole, leaf-petiole, and stem explants. Expression of Vitis vinifera GRF4-GIF1 was found to stimulate rapid organogenesis and shoot regeneration from leaf-petiole explants with plant regeneration occurring within 3-4 weeks culture on medium containing the cytokinin meta-topolin. Effects at the whole plant level were accessed by establishing plants in the greenhouse, with VviGRF4-GIF1 overexpression resulting in increased leaf size and total leaf area, and AtGRF5 stimulating above average results for plant height.